Peningkatan prestasi belajar dengan metode Problem Posing dan bantuan LKS bagi siswa kelas III SDN 03 Talun - Amat Turip (Action Research Journal, 2021)
There are several learning methods that are considered capable of improving student achievement. One of them is the problem posing method, which is a method that emphasizes student activities to make questions, discuss, complete and present the results of their work. The purpose of this study was to find out that learning mathematics with the problem posing method was effective in improving the learning achievement of social arithmetic for third grade students at SDN 03 Talun, Pekalongan. After learning mathematics with the problem posing method, significant results were obtained in increasing learning motivation, increasing activeness and ability to communicate the concepts learned. The indicators of achievement in this study were the class average score of 67.18 in the first cycle rose to 74.23 in the second cycle, classical learning completeness 59.09% in the first cycle rose to 86.36% in the second cycle, student activity 62 ,98% increased to 78.32% in the second cycle, the teacher's performance by 70% in the first cycle rose to 90% in the second cycle and student responses about learning with problem posing and LKS assistance were obtained by 86.15% in the second cycle.